Strategy for Developing Integrated Marine Transportation in the Banda Island Tourism Area (Process Hierarchy Analysis Approach) - NURLETTE, Nur Ali; RAMLY, Fahrudin; MATITAPUTTY, Izaac Tony; SANGADJI, Maryam (Journal of Tourism Economics and Policy, 2024)
The tourism sector has now become an important and strategic industry in  improving a country's economy. This is not only limited to foreign exchange income for the State, but can also increase people's economic activity, especially the home crafts industry and small industries in general. Apart from that, the hotel and restaurant industry is also growing with various other economic linkages. For Indonesia, the tourism industry plays an important role in the economy, so it is formally outlined in the Medium Term Development Plan which places the tourism industry as a strategic industry for economic growth. Then it was adopted by the Maluku Provincial Government in the 2019-2024 National Medium Term Development Plan by placing it as one of the regions in the Eastern Region of Indonesia with various potential features. This specialty is not only in terms of historical aspects but also various natural beauties and local uniqueness in terms of traditions, culture and society. The potential tourist attractions of Maluku Province in the entire area or scope of existing districts are diverse (RPJMD 2019-2024).